Study of the Antimicrobial Activity of the Human Peptide SQQ30 against Pathogenic Bacteria - Michela Di Napoli; Giusy Castagliuolo; Sara Pio; Ilaria Di Nardo; Teresa Russo; Dario Antonini; Eugenio Notomista; Mario Varcamonti; Anna Zanfardino (MDPI AG, 2024)
Given the continuous increase in antibiotic resistance, research has been driven towards the isolation of new antimicrobial molecules. Short, charged, and very hydrophobic antimicrobial peptides have a direct action against biological membranes, which are less prone to developing resistance. Using a bioinformatic tool, we chose the SQQ30 peptide, isolated from the human SOGA1 protein. The antimicrobial activity of this peptide against various Gram-negative and Gram-positive bacterial strains and against a fungal strain was studied. A mechanism of action directed against biological membranes was outlined. When administered in combination with the antibiotic ciprofloxacin and with the TRS21 (buforin II), another antimicrobial peptide, SQQ30 can be used with a lower MIC, showing additivity and synergism, respectively. Particularly interesting is the ability of SQQ30 to bind LPS in Gram-negative strains, preventing the eukaryotic cell from releasing inflammatory mediators. Our study indicates SQQ30 as a novel and promising antimicrobial agent.